THE EFFECT OF ADVERSITY INTELLIGENCE AND CAREER MATURITY ON ENTREPRENEURIAL INTENTIONS - Dedi Purwana; Rini, Lestia; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine whether there is an influence of adversity intelligence and career maturity on entrepreneurial intentions in class X SMA Negeri 59 Jakarta. This research used quantitative methods. Methods of data collection using a survey. The survey was used to obtain primary data for variable X2 (career maturity) and secondary data for variable X1 (adversity intelligence). The population reached in this study amounted to ± 245 students. Based on Isaac & Michael's table, the number of samples in this study was 142 students. The sampling technique in this study is non-probability sampling. This non-probability sampling group of population elements is selected on a voluntary basis or because of the personal considerations of the researcher that they are considered representative of the population. The technique used to determine the sample is purposive sampling. Purposive sampling technique is a sampling technique with certain considerations. For data processing, the researcher processed the questionnaire using a Likert scale. The data analysis technique using the SPSS version 24.0 program was started by looking for a requirements analysis test using the Kolmogorov-Smirnov normality test with the results of the entrepreneurship intention significance of 0,200, adversity intelligence of 0,707, and career maturity of 0,545, then using linearity test with a significance value on the linearity of adversity intelligence of 1,000, the significance value of career maturity linearity of 1,000, classical assumption test using heteroscedasticity test in Spearman' rho test with Sig. (2-tailed) adversity intelligence variable 0,217 and career maturity variable 0,522.